Sculpting fiction a collection of short stories - Cevallos, Mark Laurence N. (2012.)
This is a collection of short stories with an exploration of the writer?s creative process. The introduction mainly discusses sculpture as a metaphor and outlines the corresponding techniques, particularly in the modern art of synthetic/ceramic clay sculpting that can be applied to the writing of short fiction. There are three main techniques discussed, namely, armature construction, elimination, and accretion. Specific examples in the stories, in their writing as well as in their final form, are utilized to demonstrate how these techniques are employed. The introduction also includes personal details of the author?s introduction into the art of fiction writing.
Thesis -- Bachelor of Arts in Literature. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Short Stories; Armature construction -- Techniques; Elimination -- Techniques; Accretion -- Techniques; Sculpting Fiction